Konsep Penerapan Syariat Islam dalam Pencegahan Perilaku Menyimpang pada Remaja SMA Kota Banda Aceh - Abubakar, Abubakar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2009)
This article is purposed to know how concept, system and  obstacles  in  implementing  Syariah  (Islam  Law)  in preventing  misbehaviours  on  senior  high  school  effectively. The respondences of this research come from related agencies, either  Islam  Law  Department,  School,  Student  Organization. Data  collection  was  done  by  questionnaires,  interview, workshop. The  results  of  concept  prevention  deviate  behaviour  on teenages of Senior High School of Banda Aceh are: a)  Direct Prevention  Concept,  Direct  Prevention  Concept  is  concept  which assumed  immediately  can  prevent  misbehaviour  of  either teenages or the other age; (b)  Indirect Prevention Concept, this kind of prevention is planning and sustainable attempts which can be used to prevent also can reduce one or group’s intention to do disgraceful actions against values of Syariah (IslamLaw); (c)  Guiding  Concept,  guiding  is  an  effort  of  Syariah Department in giving and enhancing understanding to teachers and  students  regarding  with  True  Syariah  Implementation, along with sanctions faced as consequences of violationvalues; (d)  Violation  Prevention  through  Identification  of  Place  and Violation  Forms,  and  (e)  Problems  found  by  Department  of Syariah  in  Preventing  Deviate  Behaviours  Teenages  in  Senior High School Particularly.